2009
DOI: 10.1007/s12046-009-0049-2
|View full text |Cite
|
Sign up to set email alerts
|

Fractional-order integral and derivative controller for temperature profile tracking

Abstract: This paper establishes a new strategy to tune a fractional order integral and derivative (ID) controller satisfying gain and phase margins based on Bode's ideal transfer function as a reference model, for a temperature profile tracking. A systematic analysis resulting in a non-linear equation relating user-defined gain and phase margins to the fractional order controller is derived. The closed-loop system designed has a feature of robustness to gain variations with step responses exhibiting a nearly iso-dampin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The same method was also used by H. Ahn et al [97,98] for temperature profile tracking on heat flow experiments (Quanser Product). The enhanced version of MIGO (Fractional MIGO) method was used in [99,100] .…”
Section: Methodsmentioning
confidence: 99%
“…The same method was also used by H. Ahn et al [97,98] for temperature profile tracking on heat flow experiments (Quanser Product). The enhanced version of MIGO (Fractional MIGO) method was used in [99,100] .…”
Section: Methodsmentioning
confidence: 99%
“…To the best of the authors' knowledge, the FOID design technique proposed in [14] is the only reported work on optimization-based FO controller design using the gain and phase margin. The noninclusion of any approximation for nonlinear functions ensures the low deviation in achieving gain and phase margin specifications with the proposed technique.…”
Section: Soamentioning
confidence: 99%
“…In the only reported work on optimization-based design of FO controllers using gain and phase margin [14], a tuning procedure for the design of an FOID controller was proposed. The approach is applicable only to a specified class of plants.…”
Section: Introductionmentioning
confidence: 99%
“…An improved performance has already been observed with the incorporation of fractional order controllers in many engineering problems such as speed control of DC motor [14], temperature profile tracking [15], Aerofin control system [16] and in robotics [11]. A few successful implementations have also been found in automatic voltage regulator systems [17,18].…”
Section: Introductionmentioning
confidence: 99%